Pengaruh Penerapan Metode Resitasi Terhadap Prestasi Belajar Mata Pelajaran Al-Qur’an Hadist Bab Ayat-Ayat Demokrasi Kelas X MAS Al-Washliyah Pangkalan Brandan - Syarifah, Marhan Hasibuan, Khairunnisa (Pusdikra Publishing, 2022)
The background of this research is that based on the identification carried out by the researchers at the research location, namely: Learning at MAS Al-Washliyah Pangkalan Brandan is one-way, more centered on the teacher so that students become passive. The objectives of this research are: First, to find out the method of recitation in learning Al-Qur'an Hadith for class X MAS Al-Washliyah Pangkalan Brandan. Second, to find out the learning achievement of class X MAS Al-Washliyah Pangkalan Brandan students. Third, to determine the effect of the recitation method in learning Al-Qur'an Hadith on learning achievement in class X students at MAS Al-Washliyah Pangkalan Brandan. The type of research used in this study is a quantitative research method. In this study the form of the instrument used is in the form of a questionnaire using a Likert scale attitude that has been modified with the following assessments: Strongly agree (SS) score 3, Agree (S) score 2, and disagree (TS) score 1. The results of This research is: The recitation method has a significant positive effect on learning achievement, meaning that a good recitation method will be followed by an increase in student achievement in class X MAS Al-Washliyah Pangkalan Brandan. For every increase in the value of the recitation method by 1, the learning achievement of class X students at MAS Al-Washliyah Pangkalan Brandan will increase by 53.8%. This means that the better the recitation method, the higher the learning achievement of class X MAS Al-Washliyah Pangkalan Brandan students